1992
DOI: 10.2134/jeq1992.00472425002100040010x
|View full text |Cite
|
Sign up to set email alerts
|

Sediment and Nutrient Loss from Clay Soils as Affected by Tillage

Abstract: Agricultural source pollution of water resources has been a source of concern in recent years. Research is needed to define mechanisms of chemical and sediment loss in runoff from agricultural land, and to develop management practices that minimize transport of these pollutants. This study was designed to compare the effect of no‐till (NT) and conventional chisel‐till (CT) soil management on runoff water volumes, sediment loss, and N and P loss from small watersheds on a clay soil. Three NT and three CT waters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0
8

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 0 publications
7
42
0
8
Order By: Relevance
“…This indicated that less soil disturbance allows more crop residue to remain on the soil surface, which reduces soil erosion and facilitates better infiltration of precipitation. The observed reductions in sediment, PP, and TP loss with conservation (or reduction) compared to conventional tillage are supported by similar findings from field studies [37,38]. These studies also found P and sediment loss to be highly related for all tillage systems, as reduced tillage systems greatly reduce sediment-P losses and in turn TP losses.…”
Section: Assessment Of Bmps On Farm System Scenariossupporting
confidence: 70%
“…This indicated that less soil disturbance allows more crop residue to remain on the soil surface, which reduces soil erosion and facilitates better infiltration of precipitation. The observed reductions in sediment, PP, and TP loss with conservation (or reduction) compared to conventional tillage are supported by similar findings from field studies [37,38]. These studies also found P and sediment loss to be highly related for all tillage systems, as reduced tillage systems greatly reduce sediment-P losses and in turn TP losses.…”
Section: Assessment Of Bmps On Farm System Scenariossupporting
confidence: 70%
“…Diferenças entre os sistemas convencionais de preparo e plantio direto, observadas por Vieira et al (1978), foram menores que as constatadas aqui. Esses resultados estão coerentes com os de Resk (1981) e seguem também a mesma tendência dos reportados por Chichester & Richardson (1992). Valores bastante superiores aos verificados neste trabalho foram reportados por Faganello (1991), fato que pode ser explicado pelas diferenças nas condições edafoclimáticas entre os experimentos.…”
Section: Perdas De Punclassified
“…Os sistemas de plantio direto e convencional, comparados em dois solos argilosos do Texas (EUA), apresentaram efeitos semelhantes sobre as perdas de P em solução, mas as perdas de P adsorvido (sedimento) foram muito mais elevadas no sistema convencional (Chichester & Richardson, 1992). Num Latossolo Roxo, Castro et al (1986a) Os tratamentos vêm sendo aplicados desde novembro de 1987, tendo sido o solo, em outubro de 1987, corrigido quanto à acidez, fósforo, potássio e micronutrientes.…”
Section: Introductionunclassified
“…The physiological characteristics and soil environment of notillage rice cultivation are very different from those of tillage cultivation. Compared with tillage rice cultivation, the evaporation, seepage and leaching in no-tillage rice cultivation are all significantly reduced (Chichester and Richardson, 1992;Levaron, 1993;Zhang et al, 2002), which is beneficial to the water-saving cultivation of rice (Xie et al, 2007). The ammonia volatilization characteristic in no-tillage rice cultivation is not yet clear, but ammonia volatilization is positively correlated with soil pH (Song and Fan., 2003;Johnny et al, 2012), and the soil pH in notillage rice cultivation is decreasing (He et al, 2012).…”
mentioning
confidence: 99%